Inhibitory Effect of Antibiotics and Probiotics on Multidrug-Resistant Pseudomonas aeruginosa Isolates Producing Some Virulence Factors - Salam Jumaah, Ali; Suhail Zbar, Nedhaal (Al-Nahrain Journal of Science, 2024)
Antimicrobial-resistant (AMR) bacterial infection is major challenges for globle health systems. Pseudomonas aeruginosa is the most important clinical and epidemiological microorganisms.  It is the most common cause of nosocomial infections among non-fermenting, Gram-negative bacteria and the most common cause of opportunistic infections in patients with diseases. P.aeruginosa sample were collected from two hospitals (Al-Kadhimiya and Abu Ghraib Hospital) from the beginning of November to the end of December 2023, and identified using standard microbiological methods. All isolates were evaluated for the production of virulence factors (biofilm formation and protease activity). Four isolates with the highest values of virulence factors were selected for further analysis of antibiotic and probiotic susceptibility using broth dilution test. The study results revealed the presence of 27 samples of Pseudomonas aeruginosa bacteria, which is equivalent to 22.5% of the total 120 samples examined were identified. All isolates produced varying amounts of biofilm and protease. Four most virulent isolates were selected for susceptibility testing. All four isolates showed susceptibility to the tested antibiotics and probiotics, and significant growth inhibition was observed. This study revealed the presence of P. aeruginosa isolates with different virulence potential in Baghdad hospitals. Highly virulent isolates showed susceptibility to the tested antibiotics and probiotics, suggesting the need for further investigation of alternative treatment strategies besides conventional antibiotics.